Distribution of vesicular arbuscular mycorrhizal fungi in coal mine overburden dumps - JAMALUDDIN, K.K. CHANDRA * and (Indian Phytopathology, 2002)
The development of vesicular arbuscular mycorrhizal (VAM) fungi in different tree species in coal mine spoils was studied at Kusmunda in Bilaspur district of Madhya Pradesh, India. All the species (Acacia catechu, Dalbergia sissoo, Peltophorum pterocarpum, Ailanthus excelsa, Eucalyptus hybrida [E. tereticornis], Acacia auriculiformis, Pithecellobium dulce, Gmelina arborea, Acacia nilotica, Albizia procera and Cassia siamea [Senna siamea]) planted in coal mine spoils were infected with VAM fungi. The maximum % root colonization was observed in A. catechu, followed by D. sissoo in 5-year-old plants, whilst 2- and 3-year-old plants exhibited comparatively lower VAM infection. Acaulospora was the most dominant fungus in the coal mine spoils and Glomusand Gigaspora species were also common. Scutellospora and Sclerocystis were scarce in overburden spoils.